2004
DOI: 10.5367/000000004773973109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rural Women's Workload on Care Practices and Children's Growth

Abstract: The authors studied various work activities of rural women and their effects on care practices and the growth of their children. Weight for height (wasting) and height for age (stunting) were used as indicators of the growth of children and the results were compared with National Centre for Health Statistics (NCHS) recommended standards. The findings show that rural women have a heavy workload, working an average of 13 hours per day. This affects the time available for childcare, which is a major factor affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
2
6
0
Order By: Relevance
“…According to Save the Children [32], it was shown that in most developing countries, the nutritional status of under-five children is compromised by the cumulative and synergistic effects of many risk factors which include limited access to food, lack of power at the household level, and the mother's time and energy demand. Similar studies [23,33] have reported that the long-time mothers spent in farming activities was a significant risk factor for growth among their under-five children.…”
Section: Discussion Of Findingssupporting
confidence: 61%
See 2 more Smart Citations
“…According to Save the Children [32], it was shown that in most developing countries, the nutritional status of under-five children is compromised by the cumulative and synergistic effects of many risk factors which include limited access to food, lack of power at the household level, and the mother's time and energy demand. Similar studies [23,33] have reported that the long-time mothers spent in farming activities was a significant risk factor for growth among their under-five children.…”
Section: Discussion Of Findingssupporting
confidence: 61%
“…Workload based on the number of hours spent in the field per day, also revealed that 36.9%, 50.7%, and 12.4% had heavy, moderate, and light agricultural workloads respectively. Fabusoro, et al [23] in a study carried out in Ogun State, Nigeria indicated that rural women food producers have a heavy workload, working an average of 13 hours per day. The nutritional anthropometry of the underfive children of the mothers in the rural areas studied shows that the mean weight-for-age, height-for-age, and weight-for-height Z-scores were -1.247, -1.744, and -0.233 respectively.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…During this time teenagers were in charge of looking after their small siblings. Similarly, Fabusoro et al (2004) showed various hardworking conditions of rural women and their negative effects on care practices and growth of their children.…”
Section: Resultsmentioning
confidence: 97%
“…A low level of iodized salt utilization has been reported in previous studies in Ethiopia [50,51]. Even in places with adequate resources for child feeding, nutritional knowledge and factors such as reducing work overload of mothers are crucial to improve the nutritional status of children [53].…”
Section: Discussionmentioning
confidence: 95%